Ozonation as polishing treatment of mature landfill leachate - Cortez, Susana (2010)
Mature landfill leachate is typically resistant to biological processes. In order to enhance the biodegradability of a pre-treated mature landfill leachate, ozonation treatments in a lab-scale column were assayed under different ozone concentrations, contact time, initial pH, and hydrogen peroxide concentrations. Degradation of the landfill leachate by ozone was favoured at higher pH values and with the addition of H2O2, both consistent with the enhanced production of the hydroxyl radical under such conditions. The highest organic reduction and biodegradability improvement was observed with the O3/H2O2 process at 600mgH2O2 L−1. This system was able to remove 63% of chemical oxygen demand (COD), 53% of total organic carbon (TOC), 42% of aromatic content (UV254) and increased the leachate 5-day biochemical oxygen demand (BOD5) to COD ratio from 0.01 to 0.17. Ozone combined with H2O2 contributed significantly to remove and change the recalcitrant organic matter and improved leachate biodegradability, which makes this process very attractive as pre-biological treatment.